Eukaryotic transporters for hydroxyderivatives of benzoic acid - Andrea Cillingová (Nature Portfolio, 2017)
Abstract Several yeast species catabolize hydroxyderivatives of benzoic acid. However, the nature of carriers responsible for transport of these compounds across the plasma membrane is currently unknown. In this study, we analyzed a family of genes coding for permeases belonging to the major facilitator superfamily (MFS) in the pathogenic yeast Candida parapsilosis. Our results revealed that these transporters are functionally equivalent to bacterial aromatic acid: H+ symporters (AAHS) such as GenK, MhbT and PcaK. We demonstrate that the genes HBT1 and HBT2 encoding putative transporters are highly upregulated in C. parapsilosis cells assimilating hydroxybenzoate substrates and the corresponding proteins reside in the plasma membrane. Phenotypic analyses of knockout mutants and hydroxybenzoate uptake assays provide compelling evidence that the permeases Hbt1 and Hbt2 transport the substrates that are metabolized via the gentisate (3-hydroxybenzoate, gentisate) and 3-oxoadipate pathway (4-hydroxybenzoate, 2,4-dihydroxybenzoate and protocatechuate), respectively. Our data support the hypothesis that the carriers belong to the AAHS family of MFS transporters. Phylogenetic analyses revealed that the orthologs of Hbt permeases are widespread in the subphylum Pezizomycotina, but have a sparse distribution among Saccharomycotina lineages. Moreover, these analyses shed additional light on the evolution of biochemical pathways involved in the catabolic degradation of hydroxyaromatic compounds.